Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper and Statistical Appendix analyzes the reasons behind the relatively low rates of savings in Bulgaria and prospects for their evolution over the medium term. The paper argues that low saving rates largely reflect the current stage of transition-characterized by still low income levels, incomplete structural reforms, the memories of the financial and banking crises of 1996-97, and an adverse demographic structure. An analysis of prospective saving rates indicates that as the transition process advances, saving rates may increase by 5 percentage points over the medium term.